2008
DOI: 10.1088/0963-0252/17/3/035025
|View full text |Cite
|
Sign up to set email alerts
|

Repetitively pulsed atmospheric pressure discharge treatment of rough polymer surfaces: II. Treatment of micro-beads in He/NH3/H2O and He/O2/H2O mixtures

Abstract: Plasmas are increasingly being used to functionalize the surface of polymers having complex shapes for biomedical applications such as tissue scaffolds and drug delivering micro-beads. The functionalization often requires affixation of amine (NH 2 ) or O-containing groups. In this paper, results are discussed from a two-dimensional computational investigation of the atmospheric pressure plasma functionalization of non-planar and porous surfaces of polypropylene with NH x and O-containing groups. For the former… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 22 publications
4
19
0
Order By: Relevance
“…In this previous work we also found that NH* species are preferentially formed in the DBD and, to a lesser extent, in MW ammonia-containing plasmas, while N 2 * and N 2 + species form in the DBD and, preferentially, MW nitrogen plasmas. In agreement with previous works [48,49], these findings indicate that NH* species, majority in the DBD Ar + NH 3 plasmas, are more efficient than other nitrogen species for the nitrogen functionalization of polymers. The efficiency of neutral NH* species for this purpose is further supported by the results here with the beams of neutral species.…”
Section: Nitrogen Functionalization and Type Of Plasma/beam Activationsupporting
confidence: 93%
See 1 more Smart Citation
“…In this previous work we also found that NH* species are preferentially formed in the DBD and, to a lesser extent, in MW ammonia-containing plasmas, while N 2 * and N 2 + species form in the DBD and, preferentially, MW nitrogen plasmas. In agreement with previous works [48,49], these findings indicate that NH* species, majority in the DBD Ar + NH 3 plasmas, are more efficient than other nitrogen species for the nitrogen functionalization of polymers. The efficiency of neutral NH* species for this purpose is further supported by the results here with the beams of neutral species.…”
Section: Nitrogen Functionalization and Type Of Plasma/beam Activationsupporting
confidence: 93%
“…A significant difference between DBD atmospheric plasmas and low pressure MW plasmas is that, in the former case, neutral active species are more abundant than in the latter. The opposite happens with regard to the concentration of ionized species [46][47][48][49]. This has been effectively verified with our experimental setups in previous characterization studies by optical emission spectroscopy (OES) [22].…”
Section: Nitrogen Functionalization and Type Of Plasma/beam Activationsupporting
confidence: 85%
“…Moisture content in plasmas for surface modification has often been viewed as an impurity in low pressure systems and more particularly when dealing with open‐atmosphere plasma sources. However, very few studies have intentionally used water vapor as a reactive gas for plasma surface modification, and when used, only in low concentrations .…”
Section: Introductionmentioning
confidence: 99%
“…6,7,9,15,16,[24][25][26][27] Those are grafting of hydroxyl group, carboxyl group and amine groups. The modified surface showed increased hydrophilicity, enhanced wettability to the culture medium, promoted cellular responses such as attachment and proliferation.…”
Section: Resultsmentioning
confidence: 99%
“…corrosive ammonia with inert gases or nitrogen with inert gases, or special post-solution treatments. 6,14,15 Use of ammonia gas requires special corrosion protection equipment design and environmental treatment units. According to optical emission study of dielectric barrier discharge (DBD) type atmospheric pressure plasma, the intensity of nitrogen emission depended on argon flow rate owing to ambient atmosphere.…”
Section: Introductionmentioning
confidence: 99%